αB-crystallin: a Novel Regulator of Breast Cancer Metastasis to the Brain - Malin, Dmitry (2013)
PURPOSE: Basal-like breast tumors are typically (ER/PR/HER2) triple-negative and are associated with a high incidence of brain metastases and poor clinical outcomes. The molecular chaperone αB-crystallin is predominantly expressed in triple-negative breast cancer (TNBC) and contributes to an aggressive tumor phenotype in preclinical models. We investigated the potential role of αB-crystallin in brain metastasis in TNBC. EXPERIMENTAL DESIGN: αB-crystallin expression in primary breast carcinomas and brain metastases was analyzed by immunohistochemistry among breast cancer patients with brain metastases. αB-crystallin was overexpressed or silenced in two different TNBC cell lines. The effects on cell adhesion to human brain microvascular endothelial cells (HBMECs) or extracellular matrix proteins, transendothelial migration, and transmigration across a HBMEC/astrocyte co-culture blood-brain barrier (BBB) model were examined. Additionally, the effects of overexpressing or silencing αB-crystallin on brain metastasis in vivo were investigated using orthotopic TNBC models. RESULTS: In a cohort of women with breast cancer brain metastasis, αB-crystallin expression in primary breast carcinomas was associated with poor overall survival and poor survival after brain metastasis, even among TNBC patients. Stable overexpression of αB-crystallin in TNBC cells enhanced adhesion to HBMECs, transendothelial migration, and BBB transmigration in vitro, while silencing αB-crystallin inhibited these events. αB-crystallin promoted adhesion of TNBC cells to HBMECs at least in part through an α3β1 integrin-dependent mechanism. αB-crystallin overexpression promoted brain metastasis, while silencing αB-crystallin inhibited brain metastasis in orthotopic TNBC models. CONCLUSION: αB-crystallin is a novel regulator of brain metastasis in TNBC and represents a potential biomarker and drug target for this aggressive disease.